Comparative analysis of the assessment of projects by the German development bank (kfw) and the Asian development bank - S. S. Matveevskii (Вестник университета)
A comparative analysis of the project evaluation by the German Development Bank (Kreditanstalt fuer Wiederaufbau) and the Asian Development Bank (ADB) has been conducted. Common approaches and existing differences in the evaluation of banks’ projects have been revealed, the main content of the project evaluation methodology has been determined. Both banks use financial and socio-economic indicators to evaluate projects and their activities, which allow establish the rating of projects. Project evaluation allows banks to improve their activities and achieve their strategic goals. The practical experience of the German and Asian Development Banks can be used by Vnesheconombank of Russia, that is confirmed by scientific studies of Russian authors.